Limit Order Book and Commonality in Liquidity. Issue 1 (20th March 2013) - Kang, Wenjin; Zhang, Huiping
Abstract: We show that the liquidity provided by an individual stock's limit order book comoves significantly with the market aggregate limit order book liquidity. A closer look at the inside and outside liquidity provided by different parts of limit order book suggests that inside liquidity is mainly influenced by market volatility, while idiosyncratic volatility has a larger impact on outside liquidity. Hence, limit order book inside liquidity exhibits higher commonality than outside liquidity. We also show that the comovement between the stock‐level and market‐aggregate limit order book liquidity measures is related to the commonality in the overall stock market liquidity.